Modeling and simulation of paralleled series-loaded-resonant converter - Polleri, Alejandro (Institute of Electrical and Electronics Engineers, 2008)
This paper presents the development of a circuit modeling for paralleled Series Loaded Resonant (SLR) converter used in an experimental power supply to drive high voltage and high frequency medical equipment. The circuit model for each individual converter is first described. Once the complete model of an individual converter is achieved, the model is then extended to include the parallel connection. To verify the validity of model, the design of paralleled SLR using the model is explained. The component values obtained are then being used in Pspice simulations to further prove the validity of the model.